Analysis of global sumoylation changes occurring during keratinocyte differentiation. - Phillip R Heaton (Public Library of Science (PLoS), 2012)
Sumoylation is a highly dynamic process that plays a role in a multitude of processes ranging from cell cycle progression to mRNA processing and cancer. A previous study from our lab demonstrated that SUMO plays an important role in keratinocyte differentiation. Here we present a new method of tracking the sumoylation state of proteins by creating a stably transfected HaCaT keratinocyte cell line expressing an inducible SNAP-SUMO3 protein. The SNAP-tag allows covalent fluorescent labeling that is denaturation resistant. When combined with two-dimensional gel electrophoresis, the SNAP-tag technology provides direct visualization of sumoylated targets and can be used to follow temporal changes in the global cohort of sumoylated proteins during dynamic processes such as differentiation. HaCaT keratinocyte cells expressing SNAP-SUMO3 displayed normal morphological and biochemical features that are consistent with typical keratinocyte differentiation. SNAP-SUMO3 also localized normally in these cells with a predominantly nuclear signal and some minor cytoplasmic staining, consistent with previous reports for untagged SUMO2/3. During keratinocyte differentiation the total number of proteins modified by SNAP-SUMO3 was highest in basal cells, decreased abruptly after induction of differentiation, and slowly rebounded beginning between 48 and 72 hours as differentiation progressed. However, within this overall trend the pattern of change for individual sumoylated proteins was highly variable with both increases and decreases in amount over time. From these results we conclude that sumoylation of proteins during keratinocyte differentiation is a complex process which likely reflects and contributes to the biochemical changes that drive differentiation.